Short-Term Antibacterial Efficacy of Three Bioceramic Root Canal Sealers Against Enterococcus Faecalis Biofilms - Marija Šimundić Munitić; Ana Budimir; Suzana Jakovljević; Ivica Anić; Ivona Bago (University of Zagreb. School of Dental Medicine, 2020)
Objectives: The aim of the study was to evaluate the antimicrobial efficacy of three bioceramic root canal sealers against Enterococcus faecalis (E. faecalis) biofilm. Material and methods: E. faecalis bacterial suspension was grown on filter paper discs on agar plates. After the incubation period, the discs were covered with four different root canal sealers: 1) Premixing bioceramic root canal sealer (TotalFill BC Sealer); 2) Dual component bioceramic sealer (BioRoot RCS); 3) Mineral trioxide agreggate based sealer (MTA Fillapex); 4) Epoxy resin-based selar (AH Plus). After contact time of 60 minutes, the sealers were removed, and the discs were transferred into sterile tubes containing phosphate buffered saline. After serial dilutions, the aliquots of the suspension were cultivated for 24 hours. After the incubation period, the colony forming units (CFUs) were counted. Results: There were no significant differences in antibacterial efficacy between the Total Fill BC Sealer and the AH Plus sealer (p=0.386). Both sealers showed better antibacterial efficacy compared to the BioRoot RCS and the MTA Fillapex (p<0.001). Conclusion: The Total Fill BC Sealer and AH Plus had better antibacterial efficacy than the BioRoot RCS and the MTA Fillapex sealers.